ANALISIS FAKTOR-FAKTOR YANG MEMEPENGARUHI KEDISIPLINAN KERJA PEGAWAI DI PT UBJ MENGGUNAKAN REGRESI LOGISTIK ORDINAL - Muhammad Shiddieq Adjie Yudhistira; Dewi Anggraini; Aprida Siska Lestia (Universitas Lambung Mangkurat, 2023)
The Baratama Jesindo Business Limited Liability Company (PT. UBJ) is a company engaged in coal mining and has a mining business license area of 228.25 Ha. Discipline is one of the factors that affect employee performance. Work discipline is a factor that has an important role in achieving good work goals. To get good performance, employees must have high discipline. This study aims to determine the factors that influence employee discipline at PT UBJ using ordinal logistic regression analysis and explain the relationship between the level of employee discipline and factors that are statistically significant. This study uses the ordinal logistic regression method which can be used for ordinal data taken through questionnaires at PT. UBJ. The results of this study simultaneously there is no one variable that has a significant effect. Partially, it shows that the factors that have a significant effect are the Sanctions variable, the Sanctions variable affects employee discipline at PT. UBJ in general is 7%.